EGR‐1 Regulates Radiation‐Induced Apoptosis in Human Head and Neck Squamous Cell Cancer. (2nd September 2014) - Cho, Wan Seok; Lee, Jae Hun; Yoon, Tae Mi
Abstract : Objectives: (1) Investigate that early growth response‐1 (EGR‐1) expression is expressed in human head and neck squamous cancer (human HNSCC). (2) Evaluate whether EGR‐1 affects radiation‐induced apoptosis in human HNSCC and would thus serve as the proper prognostic biomolecular marker of radiation therapy. Methods: The protein expression of EGR‐1 by immunohistochemistry was investigated in human HNSCC tissues. EGR‐1 expression was evaluated at different time points after irradiation in human HNSCC cell lines. To evaluate the impact of EGR‐1 knock‐down on radiation‐induced apoptosis of human HNSCC cell lines, cell apoptosis assays using small‐interfering RNA were performed. Western blot analysis was used to assess alteration in apoptosis related protein expression after irradiation in human HNSCC cell lines. Results: EGR‐1–positive immunoreactions were observed relative to adjacent mucosal tissue in 15 tissues (58.6%) of 28 human HNSCC tissues. After 5Gy and 8Gy irradiation, EGR‐1 increased with peak activation at 2 hours. The cleaved caspase 3, cleaved caspase 7, and cleaved PARP were increased at 2 hours after irradiation. Proapoptotic protein Bax was increased at 2 hours after irradiation. EGR‐1 knock‐down cells displayed decreased radiation‐induced apoptosis, compared with control cells in cell apoptosis assay. Cleaved caspase 3, cleaved caspase 7, cleaved PARP, and Bax activation was decreased by EGR‐1 knock‐down after irradiation. Conclusions: EGR‐1 had abundant expression in human HNSCC tissue. EGR‐1 knock‐down decreased radiation‐induced apoptosis through caspase 3, caspase, 7, PARP, and Bax. EGR‐1 may play an important role in treatment response after radiation therapy in human HNSCC.